(untitled) (Historia, 2021)
The long march is the combined effort of no less than twenty-four contributors to produce a popular (nonacademic) account of the history of the liberation struggle in South Africa. In their introduction to the book the editors make it clear that unlike existing publications which deal with specific aspects of the liberation struggle, or with the politics of certain racial or national groups, The long march attempts to deal with a variety of movements, groups and institutions that took part and are still taking part in the struggle for liberation in South Africa.